Study of potential palm acid oil (PAO) from sludge palm oil mill effluent (POME) as goat’s feed - Ahmad Ridhwan, Ahmad Faisal (2019)
This study was planned to determine the base formulation of animal feed for goat from different solid waste and to investigate the effectiveness of different formulation of solid waste via the growth of goat. PAO, Napier grass, coconut waste and water lettuce were used as the sample to produce animal feed for goats. POME is produced during palm oil mill process. PAO is produced during extracted process of POME. The solid waste produced has caused the pollution problem to the environment. The solid waste undergoes composting method to produce animal feed which is useful to the growth of goat. All these samples were collected and mixed by following the guideline book of title nutrient composition of Malaysian feed materials and guides to feeding of cattle and goats by department of veterinary services ministry of agriculture and agro-based industry Malaysia. The 4 male goats aged 6 months and above were used to conduct this experiment. The average weight of goats was 23-27 Kg. Then, the goats were fed to analyse the parameters. The 3 parameters analysed were growth performance of goats, nutrient requirement by goats and body weight gain (BW). The goats were fed the formulation for continuous 120 days (14 days adaptation and 106 days evaluation). In this study, 4 formulations were used (FA, FB, FC, FD). Each formulation contains different nutrient and composition. All these samples have nutrient needed by the goat and have a big potential to produce the animal feed for goat. Results showed that goat that take formulation A has the highest growth performance and body weight gain (BW).